The Role of Brand Awareness Mediation on the Influence of Media Richness and Information Quality on Purchase Intention on MS Glow Cosmetic Products : Study of Prospective MS Glow Consumers in Denpasar City - Yosiah Sophia; Putu Saroyini Piatrini (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
The era of globalization has brought many changes, one of which is the use of social media as a communication medium used by local brands in carrying out their marketing activities. MS Glow took advantage of this opportunity to increase the use of social media to promote skin health to the public and succeeded in achieving first position in the ranking of the best-selling skincare brands in e-commerce. This achievement is not in line with the results of the pre-survey which found that the public has a minimal level of purchase intention. This research aims to analyze the influence of brand awareness in mediating media richness and information quality on purchase intention. The research design was a quantitative associative study carried out in Denpasar City which has quite high purchasing power and health awareness. There were 70 respondents who acted as samples in the research and the research instrument was distributed via the Google Form platform. Validity tests, reliability tests, and confirmatory factor analysis were carried out on the research instruments, and path and Sobel analyzes were carried out to test the research hypotheses. The results of this research are: 1) media richness has a positive and significant effect on brand awareness, 2) information quality has a positive and significant effect on brand awareness, 3) media richness has a positive and significant effect on purchase intention, 4) information quality has an effect positively and significantly on purchase intention, 5) brand awareness has a positive and significant effect on purchase intention 6) brand awareness plays a role in mediating the influence of media richness on purchase intention, and 7) brand awareness has a positive and significant influence in mediating the influence of information quality on purchase intention